1131. Point-of-Care Interactive Decision Support Tool Demonstrates Discordance Between Healthcare Practitioner Approaches and AASLD Guideline Recommendations in the Management of HBV Infection. (31st December 2020) - Hensley-McBain, Tiffany; Schwartz, Zachary; Blanchette, Jennifer; Schulz, Jenny; King, Edward; Kwo, Paul
Abstract: Background: The AASLD HBV management guidelines were updated in 2018 to include new recommendations. Patient variables that inform HBV treatment candidacy and treatment selection are complex and interconnected. To aid healthcare practitioners (HCPs) in aligning management decisions with practice guidance, we developed a Web- and app-based decision support tool, Hep B Consult. Methods: The tool enables users to specify a guideline (AASLD, EASL, or APASL) and prompts them to enter patient variables: HBV DNA/ALT levels, liver fibrosis, extrahepatic manifestations, family history of HCC or cirrhosis, pregnancy status, coinfection, and comorbidities. Users select their intended approach for the case, after which the tool displays guideline recommendations specific to that case. Cases entered from January 2019-April 2020 by users who specified AASLD guidance (N = 7106) were assessed. Results: For 32.3% of cases, the user selected "unknown" for a variable necessary to reach a guideline recommendation (Fig 1). The information most often missing was the level of fibrosis/inflammation (unknown in 16.3% of cases). HCPs' intended management approach matched the guidelines in 61.3% of cases for which a guideline recommendation was possible (Fig 2; n = 3742). Cases in which the HCP chose to monitor when treatment was indicated (11.6%) and those in which the HCP was unsure (12.2%) represented the largest discrepancies. Certain types of cases demonstrated higher discordance (Fig. 2). The intended approach did not match the guidelines for 49.2% of immune-tolerant cases (n = 128). We also identified patterns important for patient health. In 20.0% of cases with compensated cirrhosis or moderate/severe inflammation or fibrosis (n = 345) and 12.5% of cases with decompensated cirrhosis (n = 72), the HCP intended to monitor although treatment was indicated. Figure 1. Recommendation outcomes of cases entered for AASLD guidance. Figure 2. Inconsistencies between HCPs intended management practices and AASLD guidelines. Conclusion: This tool highlights important knowledge gaps in information needed to make appropriate HBV management decisions, particularly in the setting of cirrhosis. It also demonstrates differences between HCPs' approaches and the AASLD guideline recommendations. Of cases in which the HCPs' intention were inconsistent with guidelines, 52.1% indicated that they planned to change their approach after being provided the recommendation by the tool (Fig 3). Figure 3. HCPs intent to change management practice after seeing guideline recommendation. Disclosures: Jenny Schulz, PhD, Eiger Biopharmaceuticals (Other Financial or Material Support, Editorial support) Paul Kwo, MD, Abbvie (Advisor or Review Panel member)Alios (Advisor or Review Panel member)Assembly Biosciences (Research Grant or Support)Eiger (Research Grant or Support)Gilead Sciences (Advisor or Review Panel member)Janssen (Other Financial or Material Support, Data and Safety Monitoring Board)